2020
DOI: 10.3390/molecules25245873
|View full text |Cite
|
Sign up to set email alerts
|

Improving Vesicular Integrity and Antioxidant Activity of Novel Mixed Soy Lecithin-Based Liposomes Containing Squalene and Their Stability against UV Light

Abstract: In order to improve the membrane lipophilicity and the affinity towards the environment of lipid bilayers, squalene (SQ) could be conjugated to phospholipids in the formation of liposomes. The effect of membrane composition and concentrations on the degradation of liposomes prepared via the extrusion method was investigated. Liposomes were prepared using a mixture of SQ, cholesterol (CH) and Tween80 (TW80). Based on the optimal conditions, liposome batches were prepared in the absence and presence of SQ. Their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 49 publications
0
1
1
Order By: Relevance
“…The study by Temprana et al [40] has shown that changes induced by UV irradiation are sufficient to increase the size stability of liposomal populations. In contrast to our results, Toopkanloo et al [41] reported that the vesicle size of the liposomes increased due to exposure to UV irradiation and due to their photochemical destruction via absorption of photon energy and a drastic change in the liposome bilayer conformation. However, in the case of the mentioned study, liposomes contained cholesterol and Tween 80 apart from soy phospholipids, which made the liposomal bilayer more fluid and permeable and, consequently, more susceptible to UV-induced disturbing of the order and lipid packing of the membrane.…”
Section: Discussioncontrasting
confidence: 99%
“…The study by Temprana et al [40] has shown that changes induced by UV irradiation are sufficient to increase the size stability of liposomal populations. In contrast to our results, Toopkanloo et al [41] reported that the vesicle size of the liposomes increased due to exposure to UV irradiation and due to their photochemical destruction via absorption of photon energy and a drastic change in the liposome bilayer conformation. However, in the case of the mentioned study, liposomes contained cholesterol and Tween 80 apart from soy phospholipids, which made the liposomal bilayer more fluid and permeable and, consequently, more susceptible to UV-induced disturbing of the order and lipid packing of the membrane.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, there was still some polydispersity present. It has been insinuated that, for lipid nanoparticles, a PDI < 0.5 is seen as an acceptable threshold [33]. The FDA sets no recommendations regarding the PDI of liposome drug products [34].…”
Section: Discussionmentioning
confidence: 99%